The pragmatic functions of numeral classifiers in modern Malay written corpus - Khazriyati Salehuddin,; Heather Winskel,; Marlyna Maros, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Numeral classifiers are primarily used to provide semantic information about the physical and functional properties of objects, the cognitive categories of objects in a particular culture, and the perceptions of the speakers within a particular speech community towards the objects. Numeral classifiers of Chinese, Vietnamese, Japanese and Thai have been found to perform pragmatic functions as well. To identify if Malay does use numeral classifiers to perform a number of pragmatic functions, we analysed a 73,000- word modern Malay corpus targeted at both adult and young audience. Results indicate that in the modern Malay corpus, the Malay numeral classifiers perform several pragmatic functions in various contexts: they function as anaphoric and cataphoric references, as indicators of definiteness and indefiniteness, and as foregrounding mechanisms in modern Malay discourse. Using twelve instances of numeral classifier usage and omission in the modern Malay corpus, this study proposes that the absence of numeral classifiers in texts is not likely to be due to language users’ ignorance of the need to use a numeral classifier or of the correct form of numeral classifiers. On the contrary, the absence of numeral classifiers in the corpus exhibits the Malay language users’knowledge of the pragmatic functions of Malay numeral classifiers.